2012
DOI: 10.1080/10410236.2011.647621
|View full text |Cite
|
Sign up to set email alerts
|

Looking Beyond the Internet: Examining Socioeconomic Inequalities in Cancer Information Seeking Among Cancer Patients

Abstract: The gap in cancer information seeking between high-socioeconomic status (SES) cancer patients and low-SES cancer patients deserves serious attention considering the importance of information and knowledge in cancer control. We thus explored the association of SES, as measured by education, with cancer patients’ overall cancer information seeking, and with seeking from each source (i.e., the Internet, mass media, medical sources, and non-medical interpersonal sources) and across two topic categories (i.e., trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
7
39
0
Order By: Relevance
“…Existing work on source use, has linked specific source utilization to the demographic make-up of information seekers (Lee, Ramirez, Lewis-Persky, Gray, & Hornik, 2012). The Lin et al (2015) study of health search behaviors found that the role of social locators (e.g., ethnicity) is declining, in relation to psychological factors (e.g., self efficacy); they concluded that this dynamic is consistent with the profile of a ''mature'' Internet innovation, one in which the differences between adopters and non-adopters is leveling (as we might expect with older mass media).…”
Section: Information Source Usementioning
confidence: 99%
“…Existing work on source use, has linked specific source utilization to the demographic make-up of information seekers (Lee, Ramirez, Lewis-Persky, Gray, & Hornik, 2012). The Lin et al (2015) study of health search behaviors found that the role of social locators (e.g., ethnicity) is declining, in relation to psychological factors (e.g., self efficacy); they concluded that this dynamic is consistent with the profile of a ''mature'' Internet innovation, one in which the differences between adopters and non-adopters is leveling (as we might expect with older mass media).…”
Section: Information Source Usementioning
confidence: 99%
“…Seeking information and consultation for symptoms associated with rectal cancer are related to socioeconomic factors [13,14], and this may contribute to a more disadvantageous stage distribution [15]. The causal relationship of socioeconomic differences in rectal cancer survival may be out of reach for clinicians in their daily practice.…”
Section: Introductionmentioning
confidence: 95%
“…As more expensive technologies are developed, however, the divide seems to widen for newer innovations (Chakraborty & Bosman, 2005;Lee et al, 2012;Vishwanath, Finnegan, Hannan, & Luepker, 1991). Other work underscores the role of cultural factors-casting the digital divide as a function of Internet access-which favors Caucasians over Black and Hispanic populations (e.g., Dupagne & Salwen, 2005;Pew, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Although digital divide conceptions define Internet access in terms of race and class disparities (e.g., Ginossar & Nelson, 2010;Jeffres, Neuendorf, & Atkin, 2012;Laz & Berenson, 2013;Lee, Ramirez, Leis, Gray, & Hornik, 2012;Pingree & Hawkins, 1996;Rice & Katz, 2001; van Dijk, 2005van Dijk, , 2006Vigdor & Ladd, 2010;Vishwanath et al, 2006), the concept also encompasses psychological factors determining computer use (e.g., Eastin & LaRose, 2000;Han et al, 2009;Ruppel & Rains, 2012;Whitten, Kreps, & Eastin, 2009). Dupagne and Salwen (2005) emphasize the critical public policy debate driving this issue, one defined in terms of disparities in internet access among different social groups.…”
Section: Introductionmentioning
confidence: 98%